1996
DOI: 10.1116/1.588485
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional junction profiling by selective chemical etching: Applications to electron device characterization

Abstract: Articles you may be interested inComparative study of two-dimensional junction profiling using a dopant selective etching method and the scanning capacitance spectroscopy method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…An extreme case of tomography is the "Lateral SIMS" approach of von Criegern [57,58] whereby he sacrifices the depth resolution completely and performs a SIMS profile on the side of the sample. The results are somewhat ambiguous to interpret as now not a dopant distribution is determined but merely the integral over the entire depth at each spatial location.…”
Section: D-dopant Profilingmentioning
confidence: 99%
“…An extreme case of tomography is the "Lateral SIMS" approach of von Criegern [57,58] whereby he sacrifices the depth resolution completely and performs a SIMS profile on the side of the sample. The results are somewhat ambiguous to interpret as now not a dopant distribution is determined but merely the integral over the entire depth at each spatial location.…”
Section: D-dopant Profilingmentioning
confidence: 99%
“…Eliminating the use of a diluent (CH 3 COOH͒ and carrying out etching at a lower temperature ͑5°C͒ resulted in better control of the etching process. Etching carried out in the presence of a UV source enhanced the selectivity for p-type as was reported by Spinella et al 12 The ability to measure small changes in the thickness of material removed by the etching process was considered in terms of maximizing the number of thickness fringes present in a TEM micrograph of the etched region. The number of thickness fringes is directly related to the diffracting conditions used in imaging and thus is user selectable.…”
Section: Discussionmentioning
confidence: 97%
“…The selective etching of p ϩ regions requires the etching to be carried out under the influence of an ultraviolet ͑UV͒ source in order to achieve selectivity. 12 It has been suggested that the p-n junction behaves in the chemical solution like a solar cell. The large amount of free carriers generated by the light into the space-charge region of the junction are separated, and a hole current flows toward the boron-doped region.…”
Section: A Etchant Chemistrymentioning
confidence: 99%
“…Conventionally, the chemical etching delineation method has been used for 2D dopant profile observation involving selective chemical etching according to the concentration level of dopant by dipping the thin TEM specimens in the chemical etchant after their preparation [8][9][10][11][12][13][14]. After the etching, junction delineated profiles are observed by means of electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting interference pattern (hologram) can be used to recover both the phase shift and the amplitude of the transmitted wave. Recently, this technique has been employed for 2D dopant profiling of semiconductor devices [3][4][5][6][7].Conventionally, the chemical etching delineation method has been used for 2D dopant profile observation involving selective chemical etching according to the concentration level of dopant by dipping the thin TEM specimens in the chemical etchant after their preparation [8][9][10][11][12][13][14]. After the etching, junction delineated profiles are observed by means of electron microscopy.…”
mentioning
confidence: 99%